Impact of heat stress on milk yield and composition in early lactation of Holstein Friesian crossbred cattle - Chanda, T; Debnath, GK; Khan, KI; Rahman, MM; Chanda, GC (Bangladesh Journal of Animal Science, 2018)
The aim of the study was to know the effect of heat stress on milk yield and its composition of Holstein Friesian crossbred dairy cows rearing under intensive management system.Heat stress in dairy cows is caused by a combination of environmental factors i.e. temperature, relative humidity, solar radiation and air movement, etc. Grading-up of local cattle by temperate breeds for greater performance results to increase the sensitivity to heat stress. The trial was conducted during hot (May-July) and cool period (December-February) on a total of 12 crossbred dairy cows in early lactation period (first 60 days of lactation). The selected cows were divided into two groups namely as G1 (Holstein-Friesian 50% × Local 50%) and G2 (Holstein-Friesian 75% × Local 25%) and each group containing three cows of 3rd lactation in both periods of trail. Cows of each group were offered same quality and quantity of feed and reared in same management condition in both the trail periods. The mean average temperature humidity index (THI) of the stanchion barn were 70.83± 0.535 and 83.87± 0.375 in cool and hot period, respectively. The differences of THI of cool and hot season was significant (p<0.05). The average rectal temperature (0F) of G1 group was 101.51± 0.027and 102.15±0.049 in cool and hot period, respectively. On the other hand, the average rectal temperature (0F) of G2 group was 101.68± 0.035 and 102.5±0.052 in cool and hot period, respectively. The differences of rectal temperature of both groups between cool and hot season were significant (p<0.05). The average milk yield (Liter/day) of both groups was significantly (p<0.05) higher in cool period (14.92±0.019 and 19.54± 0.116 for G1 and G2 group, respectively) than in hot period (12.84±0.152 and 15±0.137 for G1 and G2 group, respectively). The milk yield of G2 group hampered more compare to G1 group due to higher THI during hot season. The milk fat, protein and lactose of both groups were significantly higher (p<0.05) during lower THI period compare to higher THI period, while the higher values of minerals detected in higher THI period but the differences were not statistically significant (p<0.05). From the result it is evident that the milk yield and composition are greatly affected by the heat stress during early lactation period. Bang. J. Anim. Sci. 2017. 46 (3): 192-197